2022
DOI: 10.3390/children9010049
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Clavicle Fractures and Congenital Pseudarthrosis Unraveled

Abstract: Clavicle fractures are commonly seen in the pediatric and adolescent populations. In contrast, congenital pseudarthrosis of the clavicle is rare. Although both conditions may present with similar signs and symptoms, especially in the very young, clear differences exist. Clavicle fractures are often caused by trauma and are tender on palpation, while pseudarthrosis often presents with a painless protuberance on the clavicle, which becomes more prominent as the child grows. Its presence may only become apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The clavicle has a medial and lateral ossification center which usually fuse around the seventh week of gestation. A congenital pseudoarthrosis can develop if this fusion does not occur, leading to a painless protuberance[ 4 ]. Eighty percent of clavicular longitudinal growth occurs from the medial physis.…”
Section: Diaphyseal Clavicle Fracturesmentioning
confidence: 99%
“…The clavicle has a medial and lateral ossification center which usually fuse around the seventh week of gestation. A congenital pseudoarthrosis can develop if this fusion does not occur, leading to a painless protuberance[ 4 ]. Eighty percent of clavicular longitudinal growth occurs from the medial physis.…”
Section: Diaphyseal Clavicle Fracturesmentioning
confidence: 99%
“…In addition, the most common cause in the pediatric population is sports and recreation 1 . This injury should not be confused with congenital pseudoarthrosis, which is a developmental malformation of the clavicle that initially presents as a painless protuberance of the distal clavicle; however, it can result in an insidious onset of pain over time 2 . Distal clavicle physeal fractures are similar to adult AC separations and have a similar classification system as AC joint separations.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…The incidence of CPC is unknown, with previous publications only stating that it is a rare condition with an unknown etiology [13,14]. Between January 2003 [15] and January 2022 [16] multiple authors reported that 200 CPC cases had been described in the literature, without updating the number of cases over this 19 years period. Alsaeed [17] stated in his review article in October 2021 that 200-300 CPC cases had been reported worldwide and DePaoli et al [13] published in 2022 that they had identified 284 CPC patients (293 clavicles) but included only 231 patients (240 clavicles) in their systematic review.…”
Section: Introductionmentioning
confidence: 99%